An automated fault-tolerant route discovery with congestion control using TFRF model for 3D network-on-chips. (8th November 2019) - Tyagi, Sapna; Agarwal, Amit; Avasthi, Vinay; Maheshwari, Piyush
As one of the principle patterns of communication technology for 3D-integrated circuit (ICs), the 3D-networks-on-chips (3D-NoCs) have lot of attention from scientific research community. 3D-NoCs has been provided as a propitious solution merging the high parallelism of network-on-chip (NoCs) interconnect paradigm with the high-performance and lower interconnect-power of three-dimensional integration circuits. For the permanent link faults, the fault-tolerant routing scheme has been regarded as an effective mechanism to ensure the performance of the 2D NoCs. In this paper, we propose a triggered fault-free route forwarding model called TFRF for 3D mesh NoCs without requiring any virtual channels (VCs).TFRF is a deadlock-free scheme by adopting a logic-based routing named TFRF guided by a turn activating rule model. The experimental results show that TFRF possesses better performance, improved reliability and lower overhead compared with the state-of-the-art reliable routing schemes.